2011
DOI: 10.1088/0022-3727/45/2/025206
|View full text |Cite
|
Sign up to set email alerts
|

Time-dependent effects of low-temperature atmospheric-pressure argon plasma on epithelial cell attachment, viability and tight junction formation in vitro

Abstract: The application of physical plasma to living tissues is expected to promote wound healing by plasma disinfection and stimulation of tissue regeneration. However, the effects of plasma on healthy cells must be studied and understood. In our experiments we used an argon plasma jet (kINPen®09) to gain insights into time-dependent plasma effects on cell attachment, viability and tight junction formation in vitro. Murine epithelial cells mHepR1 were suspended in complete cell culture medium and were irradiated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
67
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(72 citation statements)
references
References 28 publications
4
67
1
Order By: Relevance
“…One explanation for that is that different cell lines were used whereas GM00637 seems to be more sensitive to plasma application than mHepR1. Also, the weaker gas pressure used in the study of Hoentsch et al (2012) with 1.9 slm compared to 5 slm in the present study can be an explanation [50]. Still, our results reveal a strong and fast cytotoxic effect of the tested plasma jet.…”
Section: Treatment Of Human Cellscontrasting
confidence: 67%
See 1 more Smart Citation
“…One explanation for that is that different cell lines were used whereas GM00637 seems to be more sensitive to plasma application than mHepR1. Also, the weaker gas pressure used in the study of Hoentsch et al (2012) with 1.9 slm compared to 5 slm in the present study can be an explanation [50]. Still, our results reveal a strong and fast cytotoxic effect of the tested plasma jet.…”
Section: Treatment Of Human Cellscontrasting
confidence: 67%
“…Treatments for 10 s had no effects on the keratinocytes, whereas 30 s of argon plasma treatment led to a decreased number of cells which could re-attach and furthermore the expression levels of some adhesion molecules changed. However, a time-dependent decrease of cell vitality was also shown 2012 by Hoentsch et al [50]. They also treated suspended murine epithelial cells (mHepR1) in complete cell culture medium for 30, 60 and 120 s with the kINPen ® 09.…”
Section: Treatment Of Human Cellsmentioning
confidence: 72%
“…Recent studies reported that plasma affected cancer cells not only directly, but also by the indirect treatment of cells with previously prepared medium or water irradiated by plasma, termed plasma-activated medium (PAM) or plasma-activated water (PAW), respectively [8,[13][14][15]. The effectiveness of PAM promoted the potential of clinical applications of plasma medicine because PAM can be prepared in advanced and stored until use.…”
Section: Introductionmentioning
confidence: 99%
“…In these studies on clinical applications, a low dose of plasma was reported to be able to induce the proliferation of cells, while a high dose induced apoptosis in cells [4,9]. Several studies in which applications for cancer therapy were designed demonstrated that plasma treatments killed cancer cells more effectively than normal cells [10][11][12].Recent studies reported that plasma affected cancer cells not only directly, but also by the indirect treatment of cells with previously prepared medium or water irradiated by plasma, termed plasma-activated medium (PAM) or plasma-activated water (PAW), respectively [8,[13][14][15]. The effectiveness of PAM promoted the potential of clinical applications of plasma medicine because PAM can be prepared in advanced and stored until use.…”
mentioning
confidence: 99%
“…Although the mechanism of the interaction between cold plasma and cells or living tissue is still unclear 21 , several studies have reported the effects of cold plasma on key wound-related cells or sub-cells, included promoting theproliferationoffibroblasts 22 and endothelial cells 23 , as well as the growth of epithelial cells 24 , inhibiting the migration of fibroblasts 25 and their surface expression 26 , and activating integrin of fibroblasts and epithelial cells 27 . Interestingly, some of these effects are likely to be similar to the activities of natural ROS and/or NO during wound healing, particularly cold plasma's effects on the proliferation of both fibroblasts and endothelial cells 19 .…”
Section: Introductionmentioning
confidence: 99%